Prisoners` Knowledge of HIV/AIDS and Its Prevention in Kerman, Iran - Fatemeh H; Nakhaee (Tehran University of Medical Sciences, 2005)
More than 20 years after the AIDS epidemic first emerged, almost 38 millions people (range 34.6-42.3 millions) were living with HIV till the end of 2004. International figures are indicated that AIDS has become the leading cause of death in some developing countries so that about 2.3 millions deaths were happened in Sub- Saharan Africa to the end of 2003. A lot of HIV-infected people do not know that they are carriers and millions of people have no knowledge how to protect themselves against HIV infection. High-risk behaviors are common among people who are incarcerated. To evaluate the knowledge of Iranian prisoners regarding HIV and AIDS, a cross-sectional study was conducted in Kerman prison. In a sample of 350 prisoners, data were collected by using a questionnaire including three sections, the overall knowledge of HIV/AIDS, transmission ways and prevention. The mean score was calculated to assess the knowledge. Furthermore, the differences between the levels of prisoners' knowledge according to the personal characteristics were tested by Analysis of Variance and Kruskal-Wallis test. Results indicated that the prisoners had relatively high knowledge about HIV/AIDS and its modes of transmission. However, they had a lower level of knowledge about HIV/AIDS prevention. The overall knowledge of men about AIDS was significantly lower than women. Persons aged 46 years and older and illiterate inmates had the least knowledge about modes of transmission. In addition, the knowledge of illiterate prisoners about HIV/AIDS prevention was significantly lower than others. Further evaluation of attitudes and practices of Iranian prisoners and implementation of educational programs, regarding HIV/AIDS, is required.